RSM-Based Optimization of the Parameters Affecting TiO2-Mediated UV Photocatalysis of Vehicular Emissions in Enclosed Parking Garages. (6th July 2021) - Singh, Sandeep; Thind, Parteek; Verma, Manpreet Kaur; Singh, Dapinder Deep; Sareen, Arjun; Ahuja, Dheeraj; Chohan, Jasgurpreet Singh; Kumar, Raman; Sharma, Shubham; Khalilpoor, Nima; Issakhov, Alibek
Abstract : In the preceding times, the number of enclosed parking garages has increased significantly in developing nations. The toxic emissions from vehicular exhausts are expected to drastically compromise the environmental conditions of the parking garages. Subsequently, exposure of humans to these accumulated pollutants is also expected to degrade their health. Therefore, in the present investigation, efforts were made to estimate the applicability of TiO2 -mediated UV photocatalysis in degrading the concentration of vehicular emissions, viz., NOx and SO2, in the enclosed parking garages (EPGs). In this regard, an artificial EPGs' environment was created and experiments were designed using the Box-Behnken design in combination with response surface methodology. The process parameters chosen for maximizing the degradation of the pollutants were a concentration of TiO2 emulsion (20 to 120 ml/m 2 ), UV irradiance (1 to 5 mW/cm 2 ), and relative humidity (10 to 50%). Optimization of the laboratory experiments revealed that at optimal conditions of the process parameters, i.e., a concentration of TiO2 emulsion = 77.50   ml / m 2, intensity of UV irradiance = 3   mW / c m 2, and relative humidity = 43.2 %, maximum degradation of the NOx and SO2, i.e., 61.24% and 55.05%, respectively, was achieved. Further, it was revealed that relative humidity may prove to be the limiting factor while using the TiO2 -mediated UV photocatalysis in humid areas. Findings of this study may prove beneficial in urban planning as it may assist scientific auditory and local authorities in identifying the applicability of TiO2 -based photocatalysis in mitigating the impacts of vehicular emissions.